Elucidation of genetic diversity in methicillin-resistant Staphylococcus aureus isolated from cancer and non-cancer patients in Malaysia and Saudi Arabia - Ali A., Alreshidi Mateq (2013)
Methicillin-resistant Staphylococcus aureus (MRSA) is a versatile pathogen capable of causing a wide range of human diseases and became a leading cause of nosocomial infections worldwide. Cancer patients are unique cohort with multiple risk factors for MRSA infection. Since a little is known about the characteristics of MRSA strains among the hospitalized cancer patients in Malaysia and Saudi Arabia, it is important to elucidate the phenotypic and genotypic characteristics of local MRSA clones for the efficient management of infection in cancer patients. In the current study, a total of 240 nonconsecutive MRSA isolates were obtained from cancer and non-cancer patients in Malaysia and Saudi Arabia (60 each). The majority of MRSA isolates were multiresistant to more than four classes of antibiotics. Five and three antibiotic susceptibility profiles were observed among the MRSA isolates from cancer and non-cancer patients in Malaysia. For the isolates from Saudi Arabia, five and 14 antibiotic susceptibility profiles were observed among the MRSA isolates from cancer and non-cancer patients,respectively. Three isolates were vancomycin-intermediate (VISA) however, all of them were susceptible to daptomycin. Although there was no statistical significance between the susceptibility of isolates from cancer and non-cancer patients, the high level of multiple drug resistance among MRSA isolated from cancer patients in both countries was observed. In addition, the susceptibility of all MRSA isolates against three antiseptics agents; benzalkonium chloride (BAC), benzethonium chloride (BZT) and chlorhexidine digluconate (CHG) were determined. All isolates were susceptible to all tested antiseptics with MIC ranging from 0.5-2 μg/ml. Antiseptic resistance gene qacA/B was detected in 98.3% and 83.3% of the isolates from cancer and non-cancer in Malaysia respectively. For the isolates from Saudi Arabia, qacA/B was detected in 46% and 35% from cancer and non-cancer, respectively. Smr gene was detected in one isolate each from cancer and non-cancer patients in Malaysia. The carriage of qacA/B highly correlated with reduced susceptibility to CHG and BAC. Spa typing revealed four different spa types in the isolates from Malaysia. Eleven and 25 spa types were detected among isolates from cancer and non-cancer patients in Saudi Arabia, respectively including four new spa types identified in this study. All isolates from Malaysia belonged to ST239 whereas six and nine STs were detected among isolates from cancer and non-cancer patients in Saudi Arabia, respectively. Three agr types were detected in this study; the majority of MRSA isolates belonged to agr I. Agr III was detected in 25 and 17 isolates from cancer and non-cancer patients, respectively,whereas agr II was detected in five isolates from non-cancer patients in Saudi Arabia. No agr type IV was detected in this study. Virulence genes profiling showed that all strains were commonly positive for adhesion genes except ebps and bbp genes which were not detected in any isolate. Although the presence of adhesion genes slightly varied among MRSA isolates from cancer and non-cancer patients, these variations were not found to be statistically significant. In contrast, the presence of toxin genes seb, sec, seg and sei was found to be significant between cancer and non-cancer patients, these significances were not consistent between isolates from cancer and non-cancer in both countries. Relative quantitative real-time reverse transcriptase polymerase chain reaction (qPCR) assay was designed and applied in order to study the expression levels of selected genes encoding the adherence and toxins virulent factors. Relative quantification qPCR showed a significant higher expression level of common genes tested among strains isolated from cancer patients not only within the clone but also among different lineages. In conclusion, this study demonstrated that although all MRSA strains studied from cancer and non-cancer patients possessed several virulence determinants, the isolates from cancer patients were more multiresistance to antibiotics with low susceptibility towards antiseptic agents and the expression rather than carriage of virulence determinants may mediate higher pathogenicity potential. These data will aid in developing more effective infection control strategy to improve the management of MRSA infection in cancer patients.